Bölge Tanımlı Kapalı Alanlar İçin Düşük Güçlü Bluetooth Konumlama Sistemi - Güleryüz, Mustafa (Fen Bilimleri Enstitüsü, 2016)
Konum bilgisi, günlük hayatta ve endüstriyel sistemlerde sıkça gerek duyulan, kıymetli bir bilgidir. Dünya üzerindeki konumu belirleyebilmek için yıldız haritaları ve deniz fenerleri yüzyıllar boyu kullanılmış, daha sonra yerini uydulardan faydalanarak geliştirilen GPS sistemine bırakmıştır. Günümüzde GPS teknolojisi tüm taşıtlara hatta kişisel elektronik cihazlara kadar ulaşmıştır. Bu cihazlar açık alanlarda birkaç metre hassasiyetle konumunu belirleyebilse de kapalı alanlarda kişisel ya da endüstiyel cihazların konum bilgisine ihtiyaç duyulduğunda GPS teknolojisi yeterli hassasiyete ulaşamamaktadır. Kapalı alan konumlama özellikle kişisel cihazların kullanımının artması ve otonom hareket edebilen endüstriyel araçların çoğalmasıyla son yıllarda önemli araştırma konularından biri olmuştur. Geliştirilen farklı teknolojilerin birbirlerine üstünlükleri olduğu göz önünde bulundurulduğunda, farklı ihtiyaçlara yönelik en iyi çözümlere farklı teknolojilerle ulaşmak mümkündür. Bu nedenle farklı teknolojiler incelenmiş ve soruna yönelik en uygun çözüm önerilmiştir. GPS, RFID/NFC, WiFi ve BLE ile çeşitli çözümler sunulmaktadır. Farklı ihtiyaçlar için farklı çözümlere yönelmek gerekebilir, bu nedenle 4 teknoloji de kapsama alanı, maliyet, hassasiyet, erişilebilirlik ve güvenlik kriterlerine göre incelenmiştir. İncelemeler sonrasında Bluetooth Low Energy altyapısı ve RSSI ile konum tahmini tekniği kullanıma uygun bulunmuştur ve RSSI değerindeki standart sapma dikkate alınarak algoritma geliştirilmiştir. Bu tercihler ile 2 tip gezici donanım, 1 sabit donanım geliştirilmiştir. Bu donanımlar için ihtiyaca yönelik 1 yönlü, 1 yönsüz anten tasarımı yapılmıştır. Yönsüz anten için PIFA, yönlü anten için LOOP topolojileri tercih edilmiştir. Donanım yazılımları için yeni bir BLE profili oluşturulmuş, konum bilgisi haricinde cihazın çevresel koşulları ve yerel veri tabanındaki bilgiler kullanılarak gelişmiş bir sistem oluşturulmuştur. Ofis ortamında gerçeklenen sistem için sabit düğüm konumları belirlenmiş, yönlü ya da yönsüz anten tercihi yapılmıştır. Sabit düğümlerden toplanan veriler bilgisayar arayüzü ile işlenerek; hareketli düğüm konumları ve durumları periyodik kontrol edilip bölge değişimleri ve tahmini konumları incelenmiştir. Geliştirilen sistem güç tüketimi, hassasiyet, erişilebilirlik, güvenlik ve maliyet kriterlerine göre farklı sistemlerle karşılaştırılmıştır. Güç tüketimi, güvenlik, erişilebilirlik ve maliyet yönüyle güçlü; bölge tayini ve sınır algılama yapabilecek hassasiyette bir sistem geliştirilmiştir.

Location data is a valuable information which is often required both in daily life and industrial systems. Celestial maps and lighthouses had been used for centuries to estimate a specific location, subsequently were replaced with GPS, which is a location estimator developed via utilizing satellites. Nowadays GPS Technologies are embedded in almost all devices, even to the personal devices. These devices are capable of estimating location with the accuracy of a few meters error margin in the open fields. However, indoor area accuracy is not reliable enough when you need location estimation of the personal or industrial devices. Indoor location estimation has been one of the significant subjects of the researches with the contribution of the rise in the use of personal devices and autonomous self-driving industrial vehicles. Taking into consideration the superiority of the developed systems from each other, it is possible to generate the best need-based results via various technologies. Thus several technologies have been observed and the most convenient case-oriented result is submitted. Several solutions are provided by GPS, RFID/NFC, WiFi and Bluetooth LE. It may offer different solutions for varied needs. Thus, these 4 technologies have been evaluated according to coverage, cost, sensitivity, accessibility and security criteria. After analyzing, Bluetooth Low Energy infrastructure and location estimation technique via RSSI were found suitable for use, and an algorithm have been developed considering standard deviation of the RSSI value. By these preferences, 2 types of mobile hardware and 1 type of fixed hardware have been developed. 1 directional and 1 omni-directional need-oriented antenna have been designed. PIFA topology for omni-directional antenna, and LOOP technology for directional antenna were preferred. In this study, Cambrigde Silicon Radio CSR1010 is used for all BLE hardware blocks. It has a wide input voltage range from 1.8V up to 3.6V, and 900nA sleep mode current 16mA maximum communication current. With these features, it is suitable for use with a battery. It also has 12 digital inputs and outputs, 10-bit ADC, 4 PWM module, UART, I2C and SPI, 64KB of ROM and 64KB RAM with a built-in processor. It has also has good RF features: 7dbm output power and -92.5dbm reception sensitivity, 50Ω RF antenna connection with built-in balun.  Mobile node design has a 33mm*50mm*20.3mm container, a CR2032 battery could fit into the container. Mobile E-ink node has low power BLE and E-ink technology together. With this combination, light-weight and very low power design could be performed for personal ID tag. Fixed node has an BLE and Ethernet interface, and also optional 3G interface. It gathers data from mobile nodes via BLE and sends data to central software via Ethernet. Communication with mobile nodes and central software are managed by micro controller unit STM32F101RCT6. This device is not suitable for battery powered usage because of the large signalling traffic. Therefore, fixed nodes also contains AC/DC converter. According to usage purpose and locations of the device, directional or omni-directional antenna could be used for BLE communication. Omni-directional antenna has a center frequency of 2.45 GHz, providing the required 7% band width and 10dB return loss. Directional loop antenna has 2.45 GHz center frequency with 7% band width, 13dB return loss, 5.8dB gain and 120˚ orientation angle. For this study, a unique BLE profile has been developed. Including location information, a system has been created by using environmental informations and local databases of the devices.   In similar studies in this area, ideal condition in an ideal environment have been chosen for distance measurement in meter units. For closer results to ideal environment,  maximum RSSI values of the gathered information is used. In this study, instead of maximum of RSSI values, the mean value and standard deviation is taken into account in the implemented system.  RSSI value is affected by environment and moving object. Thus, distance measurement via RSSI value is not a robust solution. In this study, RSSI values are filtered with an algorithm that uses mean value and standard deviation of gathered RSSI values. Instead of calculating distance between fixed node and mobile node, location information of mobile node is determined with zones in the region. In addition to the location information, an advance system have been developed via using environmental conditions and information in the local database of nodes. Fixed node locations have been determined for the system which was performed in the office environment and either directional or omni-directional antennas have been preferred. The data generated from fixed nodes had been processed with computer interface; by controlling mobile node locations and conditions periodically, zone variance and estimated locations had been analyzed. The developed system was compared to the other systems according to power consumption, coverage, cost, sensitivity, accessibility and security a. Consequently, a strong system in the aspects of power consumption, security, accessibility and cost which is capable of sensitively performing zone assignment and border detection has been developed. The system performed in an office environment, the positions of fixed nodes determined. Two directional antennas and three omni-directional antennas are used for five fixed nodes. Collected periodical data from mobile nodes are processed by fixed nodes and location changes, entries to restricted areas and environmetal changes are  reported to the central software by fixed nodes. The system is suitable for improvement and could be used for various purposes in various fields.  BLE technology was developed to meet the needs of low-power and do not require high data transfer applications. Has expanded rapidly since 2010. Low-power and low-data rate applications are increasing rapidly with personal devices, machine to machine communication (M2M), Internet of  Things (IoT) applications with new ideas to reach all electronic devices. Location-based services are also needed for in-door applications. Navigation for indoor locations with a large area, caring in the field of life of patients, following the daily activities of athletes, inventory safety for high cost devices in hospitals and lobatories, monitoring the status of autonomous devices in the production line, examining the product of the process steps, knowing last position cases and boxes in logistics network, estimating working hours of stuff,  preventing the entry of visitors to the forbidden zones,studing of consumer behavior in stores and shopping centers could be applications with BLE for location-base services.
Bluetooth Low Energy Based Zone-defined Indoor Positioning System
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2016
Thesis (M.Sc.) -- İstanbul Technical University, Instıtute of Science and Technology, 2016
Keywords: Bluetooth; Ble; Konumlama; E-ink; Bluetooth; Ble; Indoor; Positioning; Ips; E-ink